Use of vascularised cartilage as an additional interposition in temporomandibular ankylosis surgery: Rationale, advantages and potential benefits - Jagannathan Mukund; Devale Maksud; Kesari Prashantha; Karanth Siddharth (Indian Journal of Plastic Surgery)
Context: Surgery for the release of temporomandibular joint (TMJ) ankylosis is a commonly performed procedure. Various interposition materials have been tried with varying success rates. However, none of these procedures attempt to recreate the architecture of the joint as the glenoid surface is usually left raw. Aims: We aimed to use a vascularised cartilage flap and to line the raw surface of the bone to recreate the articular surface of the joint. Settings and Design: There is a rich blood supply in the region of the helical root, based on branches from the Superficial Temporal Artery (STA), which enables the harvest of vascularised cartilage from the helical root for use in the temporomandibular joint. Materials and Methods: Two cases, one adult and the other a child, of unilateral ankylosis were operated upon using this additional technique. The adult patient had a bony segment excised along with a vascularised cartilage flap for lining the glenoid. The child was managed with an interposition graft of costochondral cartilage following the release of the ankylosis, in addition to the vascularised cartilage flap for lining the glenoid. Results: The postoperative mouth opening was good in both the cases with significant reduction in pain. However, the long-term results of this procedure are yet to be ascertained. Conclusions: The vascularised cartilage flap as an additional interposition material in temporomandibular joint surgery enables early and painless mouth-opening with good short-term results. The potential applicability of this flap in various pathologies of the temporomandibular joint is enormous.